First Significant Digits and the Credit Derivative Market During the Financial Crisis - Paul Hofmacher; Kurt Hornik (Contemporary Economics, 2013)
The Credit Default Swap (CDS) market has both been lauded for its ability to stabilize the financial system through credit risk transfers and been the source of regulatory concern due to its size and lack of transparency. As a decentralized over-the-counter market, detailed information about pricing mechanisms is rather scarce. To investigate reported CDS prices (spreads) more closely, we make use of empirical First Significant Digit (FSD) distributions and analyze daily CDS prices for European and US entities during the financial crisis starting in 2007. We find that on a time-aggregated level, the European and US markets obey empirical FSD distributions similar to the theoretical ones. Surprising differences are observed in the development of the FSD distributions between the US and European markets. Whereas the FSD distribution of the US derivative market behaves nearly constantly during the last financial crisis, we find huge fluctuations in the FSD distribution of the European market. One reason for these differences might be the possibility of strategic default for US companies due to Chapter 11 and avoided contagion effects.
Keywords: G01; 330; Benford's law; first significant digits; CDS market; financial crisis